1970
DOI: 10.1111/j.1365-2133.1970.tb15738.x
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Contact Dermatitis in Poland

Abstract: SUMMARY The results of patch tests involving 43 substances are reported. Individual contactants were tested on from 243 to 1205 patients. Comparisons are made with the results reported by the International Research Group on Contact Dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…For many years, in developed countries, nickel was regarded as the most common contact allergen, sensitizing women more often than men. 7,8 Chrome belongs to the main contact allergens; however, in most developed countries, this metal sensitizes fewer individuals than in the Polish population. In Western Europe, the decline of the incidence of allergy to nickel is shown.…”
Section: Discussionmentioning
confidence: 99%
“…For many years, in developed countries, nickel was regarded as the most common contact allergen, sensitizing women more often than men. 7,8 Chrome belongs to the main contact allergens; however, in most developed countries, this metal sensitizes fewer individuals than in the Polish population. In Western Europe, the decline of the incidence of allergy to nickel is shown.…”
Section: Discussionmentioning
confidence: 99%
“…In 1977, Camarasa [5] reported that the incidence of PPD sensiti zation among patients attending contact clinics in Spain was almost 10% (which compares with figures of 8% for North America in 1972 [6] and 15% for Poland in 1970 [7]). The Spanish Contact Dermatitis Research Group identified black rubber gloves rather than hair dyes as the principal agents responsible for inducing PPD sensi tivity.…”
Section: Discussionmentioning
confidence: 99%
“…During the years between 1948 and 1987, the frequency of contact dermatitis was determined with large collectives (on average 1517 persons) in various countries by means of patch tests (1 % or 2 % p-phenylenediamine in vaseline). On average and independent of sex or race, positive reactions were seen in 9 % of the tested persons [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Allergenic Effectsmentioning
confidence: 99%